Intragenerational mobility in the United States, Norway and West Germany : a comparative study - Allmendinger, Jutta [Verfasser] (My University, 1990)
"Retrospective data on the career trajectories of men from three countries are used to examine how contextual and indivual-level variables interactively determine mobility rates and mobility dynamics over time and across nations. The sample consists of men from West Germany, Norway, and the United States (white and black populations), all of whom were born around 1930. Separate analyses are performed for job mobility (i.e., all job transitions, whether upward, lateral, or downward) and career mobility (i.e., only those transitions that result in status gains). Results show that job mobility rates are significantly higher in the United States than in the two European nations, while career mobility rates are similar across the four populations. In addition, the processes that underlie joband career mobility dynamics found to differ substantially across nations, whichcasts doubt on the proposition of convergence theory that occupational structures become increasingly similar over time in industrialized societies." (authors' abstract) Auf der Grundlage von Daten über den Berufsverlauf von Männern in drei Ländern wird geprüft, wie situative und individuelle Merkmale wechselseitig im Zeitablauf und länderspezifisch Mobilitätsraten und -verläufe beeinflussen. Die Stichproben umfassen männliche Erwerbspersonen aus der Bundesrepublik Deutschland, Norwegen und den USA (weisse und schwarze Bevölkerung, die um das Jahr 1930 geboren wurden. (IAB2)
Mobilitätsprozesse in den USA, Norwegen und Westdeutschland.
Keywords: G 1.3.3.3 Mobilität; G 2.3.1 Arbeitsteilung & -organisation; Berufliche Mobilität; Einflussfaktor; Internationaler Vergleich; Soziale Mobilität; Quantitative Angaben